Sand training: a review of current research and practical applications - Binnie, M. J.; Dawson, B.; Pinnington, H.; Landers, G.; Peeling, P. (Journal of Sports Sciences, 2014)
Sand surfaces can offer a higher energy cost (EC) and lower impact training stimulus compared with firmer and more traditional team sport training venues such as grass. This review aims to summarise the existing research on sand training, with a specific focus on its application as a team sports training venue. Compared with grass, significant physiological and biomechanical differences are associated with sand exercise. However, evidence also exists to suggest that training adaptations unique to sand can positively influence firm-ground performance. Furthermore, the lower impact forces experienced on sand can limit muscle damage, muscle soreness, and decrements in performance capacity relative to exercise intensity. Therefore, using a sand training surface in team sports may allow greater training adaptations to be achieved, while reducing performance decrements and injuries that may arise from heavy training. Nevertheless, further research should investigate the effect of sand surfaces over a greater range of training types and performance outcomes, to increase the application of sand training for team sports.